Descending Inputs to Spinal Circuits Facilitating and Inhibiting Human Wrist Flexors - Aguiar, Stefane A.; Baker, Stuart N. (Frontiers in Human Neuroscience, 2018)
Recently we reported in humans that electrical stimulation of the wrist extensor muscle extensor carpi radialis (ECR) could facilitate or suppress the H reflex elicited in flexor carpi radialis (FCR), for inter-stimulus intervals of 30 ms or 70 ms respectively. The facilitation at 30 ms may be produced by both flexor afferents and extensor Ib afferents acting on a spinal circuit; the origin of the suppression at 70 ms is less certain. In this study, we investigated possible descending inputs to these systems. We used magnetic stimulation of the contralateral primary motor cortex, and click sound stimulation, to activate the corticospinal and the reticulospinal tracts respectively, and measured the effects on the H reflex conditioned by ECR stimulation. Corticospinal inputs reduced both the 30 ms facilitation and 70 ms suppression, indicating corticospinal inhibition of both circuits. By contrast, we failed to show any effect of clicks, either on the H reflex or on its modulation by ECR stimulation. This suggests that click-activated reticulospinal inputs to these circuits may be weak or absent.